2019
DOI: 10.3390/admsci9010020
|View full text |Cite
|
Sign up to set email alerts
|

What Form of Visibility Affects Earnings Management? Evidence from Italian Family and Non-Family Firms

Abstract: This paper addresses the issue of financial communication quality by studying the determinants of earnings management practices in family and non-family businesses. Previous literature has highlighted the effect of a company’s size, as a form of visibility, on earnings management practices. This study focuses on the analysis of the relationship between different forms of visibility—exposure to financial press, proximity to the consumer, size of assets, sales and firm age—and earnings quality. The results show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 86 publications
0
9
0
Order By: Relevance
“…Earnings management can also be carried out in order to smooth out the variability of profits, change the market's perception of the risk of investing in company securities, and, in this way, reduce the cost of capital [99].…”
Section: Discussionmentioning
confidence: 99%
“…Earnings management can also be carried out in order to smooth out the variability of profits, change the market's perception of the risk of investing in company securities, and, in this way, reduce the cost of capital [99].…”
Section: Discussionmentioning
confidence: 99%
“…The systematic leverage of knowledge and strategic flexibility for continuous strategic renewal requires that the firm has an elaborate and appropriate strategy (Kianto 2011). However, an integrated understanding of how this strategy is managed when increasing strategic renewal goals needs further assessment (Bamel and Bamel 2018), particularly considering that strategic flexibility and knowledge-management practices are conditioned by the characteristics of the organization and its members (Gavana et al 2019;Bojica et al 2017;Segaro et al 2014). In this regard, family businesses are characterized as a special form of company by their "familiness", which affects not only how they do business in general, but also how they deal with knowledge (Döring and Witt 2019) and flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Craig and Dibrell (2006); Berrone et al (2010); Neubaum et al (2012); Sharma and Sharma (2011) and Dangelico et al (2019) all conclude that family-controlled businesses are more likely than non-family firms to perform environmentally sustainable practices. Similarly, Stavrou et al (2007) and Cruz et al (2010) have reported that the employees of family firms enjoy greater job stability and better working conditions, while Cuadrado-Ballesteros et al (2017) and Gavana et al (2019) highlight these firms' greater commitment to philanthropic activities and ethical issues. Dyer and Whetten (2006) and Bingham et al (2011) supply preliminary evidence that the activities of family businesses are significantly less harmful, socially and environmentally, and other studies have reported that family firms present a greater predisposition towards CSR (Chrisman et al 2007;Dyer and Whetten 2006;Cennamo et al 2012;Campopiano and De Massis 2015;García-Sánchez et al 2020c).…”
Section: Female Directors and Csr In The Family Firm: The Moderating Effect Of The Organisational Environmentmentioning
confidence: 99%